MANAGEMENT OF GRIDHRASI W.S.R TO SCIATICA THROUGH PANCHAKARMA: A CASE REPORT (AYUSHDHARA, 2020)
Sciatica is a musculoskeletal disease with more than 10 million cases per year in India. It is a lumbar radiculopathy with mild, moderate or intense pain that radiates from lower back into right, left or both the legs. This article is a case report of a patient presenting with lower extremity weakness, lower back pain radiating towards both the legs and cramps in lower extremity. She was diagnosed for Gridhrasi and was admitted in IPD of All India Institute of Ayurveda. She was given Panchakarma treatment like Abhyanga, Rooksha Churna Pinda Swedana, Patra Pinda Swedana and Abhyantara Basti for a period of 18 days. There was 56.5% relief in her symptoms according to Rolland and Morris scale and on an average percentage according to subjective symptoms assessment criteria calculating relief in symptoms. On the basis of result it was observed that Panchakarma with proper Pathya Apathya can give satisfactory results in addition to it, if this intervention is given in acute stage then it may enhance the results.